Effects of microbubble-bodyfeeding on filtration properties of clay suspension - Yoshimoto , Akihiko; Ubukata, Hikaru; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Microscopic bubbles with diameter of 1 ~ 50 μm are generally called microbubbles and have different behaviors from ordinary bubbles. For example, very long stagnation, pressurized interior gas due to surface tension and free radical generation under water are characteristics of microbubbles. In cross-flow filtration of river water with UF membrane module, the filtration flux was increased by generating microbubbles in the water [1], while in dead-end cartridge filtration, microbubblebodyfeeding enhanced detachability of filter cake [2]. The reasons for these phenomena have not been clarified yet. In this study, we conducted mainly two constantpressure filtration experiments, i.e. filtration with a cylindrical cartridge filter and upward filtration with a planar filter. In the latter experiment, filtrate flows in the direction opposite to gravity. We compare the detachabilities of filter cake as well as filtration properties of suspensions with and without microbubbles, and discuss the effects of microbubbles on filtration process.